2009
DOI: 10.1016/j.vaccine.2009.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Altered pathogenicity, immunogenicity, tissue tropism and 3′-7kb region sequence of an avian infectious bronchitis coronavirus strain after serial passage in embryos

Abstract: In this study, we attenuated a Chinese LX4-type nephropathogenic infectious bronchitis virus (IBV) strain, CK/CH/LHLJ/04V, by serial passage in embryonated chicken eggs. Based on sequence analysis of the 3'-7kb region, the CK/CH/LHLJ/04V virus population contained subpopulations with a mixture of genetic mutants. The titers of the virus increased gradually during serial passage, but the replication capacity decreased in chickens. The virus was partially attenuated at passage 40 (P40) and P70, and was fully att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 71 publications
3
61
0
1
Order By: Relevance
“…The IBV strain Beaudette was attenuated after several hundred passages in embryonated hen's eggs [17] resulting in loss of virulence and also potential loss of immunogenicity. A similar result was observed in IBV strain CK/CH/ LHLJ/04V, the immunogenicity of which was substantially decreased after 110 passages in embryonated hen's eggs, resulting in loss of virulence to chickens [16] . However, most attenuated IB vaccine strains, such as H120, maintain their immunogenicity after adaptation to embryonated chicken eggs [12][13][14][15] , though the genomic mutations in passaged strains associated with attenuation of pathogenicity, immunogenicity, tissue tropism, and replication capacity in chicken tissues are unknown and variable, leading to differing efficacies associated with different vaccines.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…The IBV strain Beaudette was attenuated after several hundred passages in embryonated hen's eggs [17] resulting in loss of virulence and also potential loss of immunogenicity. A similar result was observed in IBV strain CK/CH/ LHLJ/04V, the immunogenicity of which was substantially decreased after 110 passages in embryonated hen's eggs, resulting in loss of virulence to chickens [16] . However, most attenuated IB vaccine strains, such as H120, maintain their immunogenicity after adaptation to embryonated chicken eggs [12][13][14][15] , though the genomic mutations in passaged strains associated with attenuation of pathogenicity, immunogenicity, tissue tropism, and replication capacity in chicken tissues are unknown and variable, leading to differing efficacies associated with different vaccines.…”
Section: Introductionsupporting
confidence: 78%
“…The initial results (data not shown) revealed that primers N (-) contained sequences consistent with those of CK/CH/LDL/97I, and reverse transcription (RT) was therefore performed with M-MLV reverse transcriptase (Invitrogen) using the primer N (-). RT procedures were performed using 40 μl of RNA in an 80-μl reaction volume, as previously described [16] . Each cDNA fragment was PCR-amplified from the RT products, as described previously [16] .…”
Section: Cloning and Sequencing Of Ck/ch/ldl/97i P5 And P115mentioning
confidence: 99%
See 3 more Smart Citations